METODE DEMONSTRASI SEBAGAI INTERAKSI EDUKATIF DALAM KOMUNIKASI DUA ARAH KISAH NABI ADAM AS - Suwarno, Suwarno; Harahap, Ahmad Yunus Mokoginta; Mukhlas, Mukhlas (TA'LIM : Jurnal Studi Pendidikan Islam, 2025)
Learning methods play an essential role in achieving learning objectives; one of the learning methods is the demonstration method by demonstrating items, events, rules, and sequences of carrying out activities, either directly or through the use of teaching media relevant to the subject or material presented. In the prophet Adam AS a story, there is a demonstration method. The purpose of this study is to describe the demonstration method as an educative interaction in two-way communication in the story of Prophet Adam AS. This study uses a library research method. The data is collected in the form of primary and secondary data from verses of the Qur'an, Hadith, and expert opinions, and then the data is analyzed using content analysis. This study found a concept in the form of a demo method that Adam used in explaining the names of all things. This shows that educative interactions are built with nuances full of methods to teach students. In addition, to teach students need first to change students' perceptions of the material and learning objectives.